Agile Leadership and Digital Mindset: Their Impact on Employee Performance through Employee Engagement - David, David; Lahindah , Laura (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
Digital transformation has fundamentally altered the paradigm of modern leadership, demanding adaptive leadership strategies that are responsive to technological and innovation dynamics. This study explores how leadership transformation in the digital era can drive an innovation culture and sustainably enhance organizational performance. Utilizing a comprehensive literature review approach, this study analyzes the evolution of leadership styles from traditional models to digital leadership, which integrates technology, virtual collaboration, and data-driven decision-making. The main findings indicate that effective digital leadership is characterized by technological adaptability, digital emotional intelligence, and competence in facilitating collaborative innovation. The integration of transformational leadership and digital competencies has been shown to significantly improve innovation capability, employee engagement, and organizational performance. This study also identifies challenges in implementation, such as the digital divide, resistance to change, and the need for digital skill development. A hybrid leadership model that combines a human-centric approach with technology-enabled processes demonstrates the highest effectiveness in creating sustainable competitive advantage. Practical implications include the importance of systematic leadership development, a digital transformation roadmap, and culture change management to optimize organizational performance in the digital age. This study contributes theoretically to the development of a digital leadership framework and provides practical guidelines for organizations undergoing digital transformation.